The effect of distension pressure on endothelial injury and vasodilatation response in saphenous vein grafts: conversion of a bypass graft to a dead pipe - Gurkan, Selami; Gur, Ozcan; Yuksel, Volkan; Tastekin, Ebru; Huseyin, Serhat; Gur, Demet Ozkaramanli; Canbaz, Suat (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction : Endothelial damage caused by high pressure applied for spasm relaxation during graft preparation is one of the most plausible theories explaining early graft failure. Aim of the study : We aimed to demonstrate the extent of endothelial damage in saphenous vein grafts distended to different pressure levels by using immunohistochemical methods and In vitro tissue baths. Material and methods : Saphenous vein grafts (SVGs) of 25 patients who underwent isolated elective CABG surgery were used in this study. By using a specific mechanism, SVGs were distended to five different pressure levels for two minutes: 0 mmHg, 50 mmHg, 100 mmHg, 200 mmHg, 300 mmHg. In vitro tissue baths and immunohistochemical examinations were performed. Results : None of the grafts distended to 300 mmHg pressure were functional in the tissue bath system. The relaxation response to carbachol of SVGs distended to 0, 50, 100 and 200 mmHg was 97.87 ± 4.47%, 98.52 ± 3.95%, 93.78 ± 3.64%, and 30.87 ± 4.11%, respectively. There were no statistically significant differences in terms of relaxation responses between samples distended to 0, 50, and 100 mmHg (p = 0.490). The relaxation response of samples distended to 200 mmHg was significantly decreased (p = 0.021). The endothelia of samples distended to 0 mmHg were almost intact in CD31 staining. Endothelial cell loss occurred at all tested distension pressures at different degrees. Conclusion: In vitro and immunohistochemical studies revealed that distending an SVG used for coronary artery bypass grafting with pressures of 100 mmHg or less results in less endothelial damage and increases graft patency.